Diagnostic value of CD138 and GATA3 in benign prostatic hyperplasia and prostate cancer - Yang Hu; Luo Dan; Yang Shikun; Lian Junbo; Huo Shuangjie; Dong Liru (Discover Oncology, 2025)
Abstract Objectives This study aimed to evaluate the diagnostic utility of GATA3 and CD138 as basal compartment markers in differentiating benign prostatic hyperplasia (BPH) from prostate cancer (PCa). Methods Immunohistochemical analysis of GATA3, CD138, CK34βE12, and P63 was performed on 131 prostate tissue samples (77BPH,54PCa). Expression profiles, sensitivity, specificity, and Cohen’s Kappa agreement were compared between markers. Results In BPH samples, nuclear expression of GATA3 and p63 showed identical positive rates (92.21%, 95%CI: 89.3–94.8%), while CD138 (antibody concentration 1:200) and CK34βE12 (antibody concentration 1:100) demonstrated cytoplasmic/membranous positivity in 96.10% (93.4–98.1%) and 93.51% (90.2–95.9%) of cases respectively. All markers exhibited complete negativity (H-score < 5) in PCa basal cells.GATA3 achieved 100% diagnostic concordance (95%CI: 97.8–100%) with p63 in both BPH and PCa (perfect agreement, κ = 1, p < 0.001 by McNemar-Bowker test). Compared to CK34βE12:In BPH: Sensitivity = 98.61% (97.2–99.4%), Specificity = 100% (NPV 96.3%);In PCa: Diagnostic accuracy = 100% (AUC 1.0);(Inter-rater reliability κ = 0.902-1.0, weighted least squares method).CD138 achieved 100% analytic sensitivity but suboptimal specificity (57.1%, 95%CI: 44.8–68.7%) in BPH when referenced against p63/CK34βE12, while achieving perfect discrimination (κ = 0.926, p = 7.6 × 10− 12) in PCa cohorts. Conclusions GATA3 and CD138 demonstrate basal compartment enrichment patterns that complement conventional markers for PCa diagnosis (accuracy 96–100%). Their nuclear (GATA3) and cytoplasmic (CD138) localization enhances reliability, particularly in cases with fixation artifacts or ambiguous morphology.